The Temporal Aspect of Precedence - Roza A. Volkova (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
The article deals with the temporal features of precedent phenomena. The author turns to this issue due to the importance of discovering, describing and recording the body of precedent units functioning in modern types of discourse in order to identify a system of material and spiritual guidelines of a linguocultural community. Precedent units, as elements of national cultural memory, are capable of accumulating and transmitting to subsequent generations the experience, traditions, values and ideals of society. Therefore, one should take into account the time frame for the functioning of these units, since they are included in the ideology of an era and invariably reflect it. The author considers the following to be the imperative factors that determine the “vitality” of precedent phenomena: functioning in the spaces of active influence discourses, presence of axiological and deontic components in the semantics of the precedent text, as well as immersiveness and regular reproduction. The implementation of the principles of multimodality as a consequence of the dominant role of the non-verbal component in modern communication ensures the involvement of several sensory receptors when perceiving precedent phenomena. This makes it possible to more fully unlock the communicative and pragmatic potential of precedent phenomena, thereby prolonging their “life cycle”. The research material includes texts from the information resource Mel (media about education and child rearing). Using the random sampling method, 25 national precedent phenomena were selected. Based on the survey of respondents from various age groups, the author comes to the conclusion that peripherally localized units in the system of precedent phenomena can, presumably, stay relevant for two or three generations of representatives of a specific linguocultural community, while the core composition of precedent phenomena remains relatively unchanged.